Comparison of efficacy and prognosis between neoadjuvant chemotherapy and adjuvant chemotherapy in penile cancer patients with regional lymph node metastasis - You, Ruijian; Ji, Yongpeng; Yang, Xiao; Zhao, Qiang; Cao, Yudong; Ma, Jinchao; Yu, Ziyi; Cui, Yushuang; Ma, Jinduo; Li, Ruojing; Miao, Liuyang; Yang, Yong; et al. (Frontiers in Oncology, 2025)
IntroductionThe comparative efficacy of neoadjuvant chemotherapy (NAC) and adjuvant chemotherapy (AC) in patients with lymph node metastatic penile squamous cell carcinoma (PSCC) remains unclear. This study aims to evaluate the differences in efficacy and survival outcomes between NAC and AC in PSCC patients with lymph node metastasis.MethodsWe conducted a retrospective analysis of penile cancer patients treated at Peking University Cancer Hospital between May 2015 and December 2023. All patients had lymph node metastasis and underwent lymph node dissection. 11 patients received NAC, while 14 received AC. Kaplan-Meier survival curves and multivariate Cox regression models were used to analyze baseline characteristics, progression-free survival (PFS), overall survival (OS), and associated risk factors.ResultsThere was no statistical difference in the baseline characteristics of patients between the two groups. In the NAC group, 4 patients achieved partial response (PR), 1 achieved complete response (CR), 4 achieved progression disease (PD), and 2 had stable disease (SD). After a median follow-up of 65.1 months, the NAC group had a shorter PFS compared to the AC group (P = 0.029), while no significant difference was observed in OS (P = 0.268). Multivariate Cox regression analysis identified the presence of cM stage as an independent predictor of both PFS and OS.ConclusionPenile cancer with lymph node metastasis typically carries a dismal prognosis. NAC substantially diminishes tumor size and facilitates surgical excision, whereas AC is more effective in controlling postoperative tumor progression. However, there was no significant difference in overall survival between the two treatment strategies.